Revitalisasi Desa Adat Budaya Hibua Lamo di Desa Kakara Lamo Kecamatan Tobelo Kabupaten Halmahera Utara: Revitalisasi Desa Budaya Hibua Lamo Di Desa Kecamatan Tobelo Kabupaten Halmahera Utara - Muhammad Rizal Syawal; Ernawati Hendrakusumah (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract.Kakara Lamo Village is one of the oldest traditional villages in Tobelo District, North Halmahera Regency. The traditional cultural village of Hibua Lamo Kakara Lamo which is still completing the Hibua Lamo culture to this day. In Hibualamo culture includes the system of government, kinship and marriage systems. This system is regulated in the daily life of the community in every hoana (village), especially the village of Kakara Lamo. But in fact the traditional village of Kakara Lamo is currently experiencing degradation or setback in terms of social, political, physical and cultural. The fear that will happen to the traditional village of Kakara Lamo like other villages is the fading of the Hibualamo culture and resulting in the closure of the traditional village to become an ordinary village in order to maintain cultural values and maintain them by revitalizing them. The research method is qualitative research using an explorative approach. To find out the elements of Hibua Lamo culture and the factors that decrease the existence of Hibua Lamo culture in the traditional village of Kakara Lamo. Factors decreasing the existence of the Kakara Lamo traditional village, namely the change of indigenous peoples to a more modern society, mutual cooperation changes in society due to economic factors, traditional ceremonies are less participatory for indigenous peoples, Halu traditional houses are damaged, outside culture causes modern changes in art and culture and marriage system. The revitalization of the Kakara Lamo Traditional Village is to revive the cultural identity of Hibualamo which is experiencing decline. Based on the results of the research above, the elements that need to be revitalized are carrying out adat, halu traditional houses, traditional ceremonies, and cultural arts. These revitalization steps can only take place if they have the support of indigenous peoples, local government and the role of traditional institutions as local institutions that control the lives of indigenous peoples so that they can maintain cultural identity in the traditional village of Kakara Lamo. The support of the Kakara Lamo indigenous people in the revitalization of their traditional villages determines the final outcome. Therefore, the role of indigenous peoples is very important so that the revitalization of the Kakara Lamo traditional village is carried out. Abstrak. Desa Kakara Lamo merupakan salah satu desa adat yang tertua di Kecamatan Tobelo Kabupaten Halmahera Utara. Desa adat budaya Hibua Lamo Kakara Lamo yang masih melestarikan budaya Hibua Lamo hingga saat ini Dalam budaya Hibualamo meliputi sistem pemerintahan, sistem kekerabatan dan perkawinan. Sistem tersebut diatur dalam kehidupan sehari-hari bermasyarakat di setiap hoana (kampong) terutama kampung Kakara Lamo. Tapi kenyataanya desa adat Kakara Lamo saat ini mengalami degradasi atau kemunduran dari segi sosial, politik, fisik, dan budaya. Ketakutan yang akan di alami desa adat Kakara Lamo seperti desa lainnya hilangnya budaya Hibualamo dan mengakibatkan perpindahan desa adat menjadi desa biasa agar dapat mempertahankan nilai budaya dan melestarikannya dengan melakukan revitalisasi. Metode Penelitian yaitu Penelitian kualitatif dengan menggunakan pendekatan Eksploratif. Untuk mengentahui elemen-elemen budaya Hibua Lamo dan faktor-faktor penurunan eksistensi budaya Hibua Lamo di desa adat Kakara Lamo. Faktor-faktor penuruanan eksistensi desa adat Kakara Lamo yaitu perubahan masyarakat adat ke masyarkatan yang lebih modern, gotong royong perubahan masyarakat karna faktor ekonomi, upacara adat kurang partisipatif masyarakat adat, rumah adat Halu mengalami kerusakan, Budaya luar yang menyebabkan perubahan modern dalam seni budaya dan sistem perkawinan. Revitalisasi Desa Adat Kakara Lamo adalah menghidupakan kembali identitas budaya Hibualamo yang sedang mengalami kemunduran. Berdasarkan hasil peneleitian di atas maka elemen-elemen yang perlu direvitalisasi yaitu permukiman adat, rumah adat halu, upacara adat, dan seni budaya. Langkah-langkah revitaliasi ini baru bisa terjadi jika mendapat dukungan masyarakat adat, pemerintah daerah dan peran lembaga adat sebagai institusi lokal yang mengotrol kehidupan masyarakt adat agar dapat menjaga identitas budaya di desa adat Kakara Lamo. Dukungan masyarakat adat Kakara Lamo dalam revitalisasi desa adat menjadi penentu hasil akhir. Oleh karna itu peran masyarakat adat sangat penting agar terlaksana revitalisasi desa adat Kakara Lamo.